PENGEMBANGAN MEDIA BERBASIS GENIALLY PERMAINAN ULAR TANGGA PADA MATERI STANDAR PELAYANAN CUSTOMER SERVICE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI BISNIS RITEL DI SMK ADHIKAWACANA SURABAYA - Irma Tri Mustika; Veni Rafida (Jurnal Pendidikan Tata Niaga (JPTN), 2026)
This research was motivated by the low learning outcomes of Grade XI Retail Business students at SMK Adhikawacama Surabaya, where 69% had not achieved the Minimum Mastery Criteria (KKM) on Customer Service Standards material due to lecture-based methotds and non-interactive media. This study aimed to develop a Genially-based snakes and ladders game media, measure its feasibility, and analyze students’learning outcome improvement. The Research and Development (R&D) method with the 4D model was employed, involving 30 students of Grade XI Retail Business 2 as trial subjects. The results showed that the media was feasible with an average expert validation of 80,33%, practical based on student response questionnaires at 81,60% categorized as “Very Positive”, and effective in improving learning outcomes with an average N-Gain Score of 0,379 categorized as “Moderate”.